The Effect Of Intellectual Capital Towards Firm’s Financial Performance, Moderating Effect Of Firm Reputation - Angela, Clara; Gusti Agung Musa Budidarma, I (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to analyze the impact of intellectual capital on the financial performance of companies in Indonesia, considering the moderating effects of corporate reputation as presented by Fortune 100 Indonesia list. Intellectual capital, which includes employee capital and structural capital, is considered an important asset that can enhance a company's financial performance. The study uses secondary data from the annual reports of companies listed on the Fortune 100 and Indonesia Stock Exchange for the period of 2020 to 2022. The analysis method employed is data panel regression analysis, and purposive sampling is used in forming the sample. The results of regression analysis shows support for the significant impact of intellectual capital towards financial performance, urging Indonesian firms to maintain their intellectual capital well. On the other hand, firm size may also be inspected as independent variable instead of moderator.